Investigation of the parameters governing the performance of jet impingement quick food freezing and cooling systems – a review - Marazani, Tawanda; Madyira, Daniel M.; Akinlabi, Esther T. (Elsevier, 2022)
Jet Impingement Technology (JIT) is a heat transfer enhancement technique. Available literature soundly confirm its wide applications in the cooling of combustion chambers, critical parts of turbines, glass technology, electronic components, drying of paper and textile materials, drying of biomaterials and food preservation. The technology has interesting fluid dynamics and heat transfer properties. Its relative simplicity and low cost, abundance of air, generation of high heat transfer and faster freezing rates have made it a subject of extensive investigations. Several investigations on jet impingement quick food freezing and cooling systems which range from visualization, experimental, computational simulations and or numerical analysis, factorial and mathematical models have been studied. This paper reviews the governing parameters of the jet impingement quick food freezing and cooling systems.